Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/adfm.200500032
|View full text |Cite
|
Sign up to set email alerts
|

Organic Solid Solutions: Formation and Applications in Organic Light‐Emitting Diodes

Abstract: To enhance the performance of organic devices, doping and graded mixed‐layer structures, formed by co‐evaporation methods, have been extensively adopted in the formation of organic thin films. Among the criteria for selecting materials systems, much attention has been paid to the materials' energy‐band structure and carrier‐transport behavior. As a result, some other important characteristics may have been overlooked, such as material compatibility or solubility. In this paper, we propose a new doping method u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…[1][2][3][4] The benefits of doping organic materials for e.g. OLED applications, 12 and of mixing n and p-type semiconductors in ambipolar transistors 13,14 have also been reported, as well as more fundamental studies on the structure of functional blends. 15 P-terphenyl and pentacene have similar crystal structures with one monoclinic and the other triclinic respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The benefits of doping organic materials for e.g. OLED applications, 12 and of mixing n and p-type semiconductors in ambipolar transistors 13,14 have also been reported, as well as more fundamental studies on the structure of functional blends. 15 P-terphenyl and pentacene have similar crystal structures with one monoclinic and the other triclinic respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Organic compounds have been extensively investigated in the fabrication of various electronic and photonic devices in the last two decades [1]. Some of the advantages of organic materials include flexibility in the methods of synthesis, scope for altering the properties by functional substitution and inherently high nonlinearity [2].…”
Section: Introductionmentioning
confidence: 99%
“…[4,[17][18][19] When two or more materials are used in a blend, the material compatibility or mutual solubility is one of the keys to high-performance devices, especially for long-time operation. [20,21] Therefore, the proper selection of organic material components is an important issue. We found that MATS shows excellent compatibility with superyellow.…”
mentioning
confidence: 99%